2012
DOI: 10.1021/ic302322r
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of Ln(III) Complexes with Macrocyclic Ligands Through Theoretical Evaluation of 1H NMR Contact Shifts

Abstract: Herein, we present a new approach that combines DFT calculations and the analysis of Tb(III)-induced (1)H NMR shifts to quantitatively and accurately account for the contact contribution to the paramagnetic shift in Ln(III) complexes. Geometry optimizations of different Gd(III) complexes with macrocyclic ligands were carried out using the hybrid meta-GGA TPSSh functional and a 46 + 4f(7) effective core potential (ECP) for Gd. The complexes investigated include [Ln(Me-DODPA)](+) (H(2)Me-DODPA = 6,6'-((4,10-dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
64
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(74 citation statements)
references
References 88 publications
10
64
0
Order By: Relevance
“…Figure represents the molecular geometries of the [Eu 2 L 2 ] 2+ and [Eu 3 L 3 ] 3+ complexes calculated at the HF/LCECP/3‐21G level. The solid‐state and solution structures of the [Ln L 1 ] + complexes have been reported in previous works , . Herein, theoretical calculations were carried out to estimate the intramolecular Ln ··· Ln distances in the binuclear and trinuclear [Ln 2 L 2 ] 2+ and [Ln 3 L 3 ] 3+ entities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure represents the molecular geometries of the [Eu 2 L 2 ] 2+ and [Eu 3 L 3 ] 3+ complexes calculated at the HF/LCECP/3‐21G level. The solid‐state and solution structures of the [Ln L 1 ] + complexes have been reported in previous works , . Herein, theoretical calculations were carried out to estimate the intramolecular Ln ··· Ln distances in the binuclear and trinuclear [Ln 2 L 2 ] 2+ and [Ln 3 L 3 ] 3+ entities.…”
Section: Resultsmentioning
confidence: 99%
“…In previous works,, it has been shown that the macrocyclic ligand H 2 L 1 (Scheme ) forms eight‐coordinate complexes with Ln ions both in the solid state and in solution. The presence of the methyl substituents in positions 1 and 7 of the cyclen moiety introduces a certain degree of steric hindrance on the picolinate pendants that prevents the coordination of water molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The hard nature of the metal ion is more evident in the case of the Eu 3+ and Lu 3+ complexes reported previously, for which the bond distances involving the oxygen atoms of the ligand are even shorter when compared to the distances to nitrogen atoms. 30 The distances between Bi and the donor atoms of the cyclen unit are ca. 0.1 Å longer than the average Bi−N distance observed for [Bi(dota)] − (2.53 Å).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[11] Susceptibility tensor fitting results (Figure 1) ] complexes reconstructed by Spinach [9] using the best-fit magnetic susceptibility tensor. Positive PCS is shown in red, negative -in blue, transparency indicates the absolute value normalized for all complexes (see the ESI for further information).…”
Section: Beyond Bleaney's Theory: Experimental and Theoretical Analysmentioning
confidence: 99%